Efficient removal of ciprofloxacin from pharmaceutical wastewater using advanced oxidation processes on doped perovskite La₀.₅A₀.₅CoO₃ (A = Sr, Ba and Ce) nanocatalysts - Mohammad Ali Jalali; Seyed Mahdi Mousavi; Moslem Setoodehkhah (Applied Catalysis O: Open)
In this research, to improve the efficiency of pharmaceutical wastewater treatment processes, perovskite nanocatalysts LaCoO₃ and its doped La₀.₅A₀.₅CoO₃ (A = Sr, Ba and Ce) were synthesized and investigated as persulfate activation catalysts to remove ciprofloxacin. Characterization and identification of these nanocatalysts were done using advanced techniques such as (XRD), (SEM), (DLS), (BET) and (FT-IR). Characterization results indicated higher phase purity of the La₀.₅Sr₀.₅CoO₃ sample, which positively affected the catalytic performance in persulfate activation. The effects of operating variables, including temperature, pH, catalyst amount, and oxidant dosage, on the decomposition process were investigated using experimental design and response surface methodology. Results showed that by adding 0.1 g of La₀.₅Sr₀.₅CoO₃ catalyst to 100 mL of a solution containing ciprofloxacin at a concentration of 10 ppm for 120 min, 91 % of the ciprofloxacin was degraded. By optimizing the operating conditions through experimental design, the performance of this catalyst was improved to 98.5 %. The application of the La₀.₅Sr₀.₅CoO₃ catalyst for ciprofloxacin removal offers several advantages over other methods reported in the literature, including mild reaction conditions, high degradation efficiency, and rapid reaction times.